What would primary care practitioners do differently after a delayed cancer diagnosis? Learning lessons from their experiences - Tuomas H. Koskela; Magdalena Esteva; Marcello Mangione; Sara Contreras Martos; Senada Hajdarevic; Cecilia Högberg; Mercè Marzo-Castillejo; Jolanta Sawicka-Powierza; Vija Siliņa; Michael Harris; Davorina Petek (Taylor & Francis Group, 2024)
AbstractObjective Diagnosis of cancer is challenging in primary care due to the low incidence of cancer cases in primary care practice. A prolonged diagnostic interval may be due to doctor, patient or system factors, or may be due to the characteristics of the cancer itself. The objective of this study was to learn from Primary Care Physicians' (PCP) experiences of incidents when they had failed to think of, or act on, a cancer diagnosis.Design A qualitative, online survey eliciting PCP narratives. Thematic analysis was used to analyse the data.Setting and subjects A primary care study, with narratives from 159 PCPs in 23 European countries.Main outcome measures PCPs' narratives on the question 'If you saw this patient with cancer presenting in the same way today, what would you do differently?Results The main themes identified were: thinking broadly; improvement in communication and clinical management; use of other available resources and 'I wouldn't do anything differently'.Conclusion (Implications) To achieve more timely cancer diagnosis, PCPs need to provide a long-term, holistic and active approach with effective communication, and to ensure shared decision-making, follow-up and continuing re-assessment of the patients' clinical conditions.